Ultralow dose computed tomography protocol for hook‐wire localization of solitary pulmonary nodules prior to video‐assisted thoracoscopic surgery. Issue 6 (1st May 2019) - Liu, Bo; Fang, Jie; Jia, Haipeng; Sun, Zhigang; Liao, Jian; Meng, Hong; Pan, Fengmin; Li, Chunhai
Abstract : Background: This study prospectively investigated the efficacy and radiation dose of ultralow dose computed tomography (CT)‐guided hook‐wire localization (HWL) at 100 kV with tin filtration (100Sn kV) for small solitary pulmonary nodules. Methods: All HWL procedures were performed on a third generation dual‐source CT system. Eighty‐eight consecutive patients undergoing CT‐guided HWL were randomly assigned to standard dose CT (Group A: n = 44; reference 110 kV and 50 mA) or ultralow dose CT (Group B: n =44; 100 Sn kV and 96 mA) protocols. The technical success rate, complications, subjective image quality, and radiation dose were compared between the groups. Results: The mean volume CT dose index and total dose‐length product were significantly lower in Group B compared to Group A (0.32 mGy vs. 3.2 ± 1.1 mGy and 12.1 ± 0.97 mGy‐cm vs. 120 ± 40.6 mGy‐cm; P < 0.001). The effective dose in Group B was significantly lower than in Group A (0.17 ± 0.01 mSv vs. 1.68 ± 0.57 mSv, ‐89.8%; P < 0.001). The technical success rates were 100% for both groups. There were no significant differences in complication rates between the protocols ( P > 0.05). The image quality of ultralow dose CT met the requirements for HWL procedure. Conclusion: Ultralow dose CT‐guided HWL of solitary pulmonary nodules performed at 100 Sn kVp spectral shaping significantly reduced the radiation dose compared to standard dose CT, with high technical success and acceptable patient safety.